Bonding With Parents, Body Image, and Sociocultural Attitudes Toward Appearance as Predictors of Eating Disorders Among Young Girls - Izydorczyk, Bernadetta; Sitnik-Warchulska, Katarzyna; Wajda, Zbigniew; Lizińczyk, Sebastian; Ściegienny, Aleksandra (Frontiers in Psychiatry, 2021)
A more holistic approach to treatment and prevention focuses on identifying the multiple risk and protective factors for eating disorders. However, there is a lack of research verifying the nature of the relationship between patterns of bonding with parents, sociocultural attitudes toward appearance, body image, and their role in developing or preventing eating disorders. The main aim of the study was to verify whether there is a specific set of risk or/vs. protective factors/measures for behaviors and dispositions related to the development of eating disorders. The study group consisted of 134 young Polish females (M = 14.92; SD = 1.349), with an average body mass index. The variables were measured using the Parental Bonding Instrument, the Sociocultural Attitudes Toward Appearance Questionnaire-3, The Multidimensional Body–Self Relations Questionnaire, and the Eating Disorder Inventory 3. Stepwise regression analysis was applied. Statistical analysis showed that bonding with parents (including maternal overprotection), body image (including overweight pre-occupation, fitness evaluation, health orientation, and self-classified weight), and sociocultural attitudes toward appearance (such as searching for information, pressures, and internalization) are predictors of eating disorder risks. On the other hand, maternal and paternal care (aspects of patterns of bonding with parents), positive fitness evaluation, positive appearance evaluation, and satisfaction with one's body were found to be the most significant protective factors. The results may improve prevention and intervention aimed at increasing protective factors.